The Final Offer in the Chilean Electrical Panel - Carrasco Delgado, Nicolás (2018)
Efficient solutions are difficult to adopt, as they comprehend a large amount of information and require identifying an optimum point, which weighs up the benefits and costs involved. One means of simplifying this task arises with the final offer rule (the judge accepts the position of one or the other part, in a complete way). The Chilean electricity system provides for a rule of this nature to rule on disputes, which come before the so-called «electrical panel». This article will discuss the rule’s considerations of efficiency and the complexities, which the final offer presents for traditional procedural principles. A rule acclaimed by economists for taking decisions could cause lawyers to reconsider the mechanisms for resolving certain disputes.